Stepping Forward: Personality Traits, Choice of Profession, and the Decision to Become Self-Employed - Alina Sorgner; Michael Fritsch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We argue that entrepreneurial choice proceeds in at least two steps, with vocational choice nearly always preceding choice of employment status, whether that be self-employment or dependent employment. Since the two decisions are interrelated, analysis of entrepreneurial choice as a single act may lead to inconsistent estimates of the factors that determine the decision to launch a business venture. Our empirical analysis utilizes a bivariate probit model that jointly estimates both decisions. The results support our argument that entrepreneurial choice is a two-stage decision process.
Keywords: L26; J24; D01; 330